Measurement methods of physical activity in investigation associated with assessment of quality of life in elder adults - Kurysh N.O (Kharkov National Pedagogical University, 2012)
Analysis of publication in physical activity measurement methods is provided. Presented three groups of physical activity measurement methods criterion, objective, subjective methods. Established that criterion methods are more accurate and used for validate objective and subjective methods. Subjective methods frequently used in investigation of youth and elderly population. Advisability of IPAQ questionnaire in international physical activity investigation of elderly adults is substantiated.